Environmental determinants of the abundance of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Weldon, Christopher W. (University of Pretoria, 2021)
Dissertation (MSc (Entomology))--University of Pretoria, 2021.